Reliability of a Centroid method to estimate head position in cephalometric diagnosis - Hideo SUZUKI; Selly Sayuri SUZUKI; Aguinaldo Silva GARCEZ; Juliana Mandello CARVALHAES; Denise Nami FUJII; Ynara Bosco LIMA-ARSATI (Faculdade São Leopoldo Mandic, 2020)
ABSTRACT Objective The objective of this study was to 1) evaluate the reproducibility of natural head position (NHP) in different professional groups; 2) compare three cephalometric methods of estimating head position to the established natural head position and 3) investigate the applicability of a new method to estimated head position using a Centroid method. Methods The sample consisted of 105 individual cephalometric tracings and photographs. For the first evaluation, copies of the lateral photographs were reproduced for each patient and 3 professionals with different expertise (experienced orthodontists, orthodontic students and orthognatic surgeon) were instructed to position the photographs in NHP. Later, 3 different methods to obtain NHP were assessed: 1) the Frankfort Horizontal Plane (FRANK), 2) Sella-Nasion 7º Line (SN7) and 3) proposed Horizontal Reference Line based on Centroid. Angles formed by the evaluated planes/lines and True Vertical Line obtained were measured. Gender and skeletal discrepancy were considered. Results The results showed a significant difference between NHP obtained from orthodontists and surgeons compared to students (p<0.0001). Also results showed no effect of skeletal classification and gender did on measurement (p>0.05). Both SN minus 7º and FRANK methods showed a high variability (p < 0,01) compared to Centroid method. Conclusion NHP may be affected by the professional experience. The proposed horizontal line based on Centroid is a valid method for estimating head position, thus, may be indicated to use as a diagnostic tool in Orthodontics and Orthognatic Surgery.